2007
DOI: 10.1002/dvdy.21127
|View full text |Cite
|
Sign up to set email alerts
|

Expression survey of genes critical for tooth development in the human embryonic tooth germ

Abstract: In the developing murine tooth, the expression patterns of numerous regulatory genes have been examined and their roles have begun to be revealed. To unveil the molecular mechanisms that regulate human tooth morphogenesis, we examined the expression patterns of several regulatory genes, including BMP4, FGF8, MSX1, PAX9, PITX2, and SHOX2, and compared them with that found in mice. All of these genes are known to play critical roles in murine tooth development. Our results show that these genes exhibit basically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 30 publications
4
50
0
3
Order By: Relevance
“…Also, a study with human embryonic tissue revealed a few differences in gene expression patterns-for example, PAX9 is not exclusively expressed in tooth bud mesenchyme but is also found in the dental epithelium (Lin et al, 2007). Ultimately, we will have to find valid in vitro assays that may help to interpret mouse data on a human background.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a study with human embryonic tissue revealed a few differences in gene expression patterns-for example, PAX9 is not exclusively expressed in tooth bud mesenchyme but is also found in the dental epithelium (Lin et al, 2007). Ultimately, we will have to find valid in vitro assays that may help to interpret mouse data on a human background.…”
Section: Discussionmentioning
confidence: 99%
“…The pathway includes genes encoding the actual signals, their receptors and mediators of signaling pathways and transcription factors. These genes primarily were associated with major interactions and process involved in development and maturation of teeth namely Msx gene, Pax gene, Shh gene, Wnt/ beta -Catenin signaling, Cbfa-1 gene [36][37][38][39] [Table/ Fig-6]. …”
Section: Genetic Factorsmentioning
confidence: 99%
“…The significance of the gene was recognized in the fact that Msx1 creates modulation to cap stage through various stages of ectomesenchyme proliferation and condensation [37]. Mice defects for Msx 1 and 2 results in failure of epithelial mesenchymal interactions and defects like anodontia or hypodontia and cleft palate occur.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…, are among them, but MSX1 seems to be of a special significance as it appears to play the most important role during early tooth development (Lin et al 2007). In fact, there are the PAX9, AXIN2 and MSX1 genes, which are evidenced to be implicated in non-syndromic agenesis (Vieira et al 2004;Letra et al 2008) The MSX1 gene is located on the chromosome 4 and belongs to the homeobox Msx gene family related to the Drosophila msh-like gene family.…”
Section: Bmp4 Fgf8 Msx1 Pax9 Axin2 Pitx2mentioning
confidence: 99%